Mechanisms of auditory perceptual learning - Jones, Peter R. (2013)
Practice improves performance on many basic auditory tasks. However, while the phenomenon of auditory perceptual learning is well established, little is known about the mechanisms underlying such improvements. What is learned during auditory perceptual learning? This thesis attempts to answer this question by applying models of performance to behavioural response data, and examining which parameters change with practice. On a simple pure tone discrimination task, learning is shown to primarily represent a reduction in internal noise, with encoding efficiency, attentiveness and bias appearing invariant. In a more complex auditory detection task, learning and development are also shown to involve improvements in listening strategy, with listeners becoming better able to selectively-attend to task-relevant information. Finally, task performance is potentially constrained not just by the strength of the sensory evidence, but also by the efficiency of the wider decision process that the sensory evidence informs. Thus, in the final chapters learning is also shown to involve reductions in both stationary and nonstationary bias.